2000
DOI: 10.21273/hortsci.35.1.63
|View full text |Cite
|
Sign up to set email alerts
|

Irrigation Criteria for Drip-irrigated Onions

Abstract: Long-day onion (Allium cepa L. `Vision') was subjected to five soil water potential (SWP) treatments (–10, –20, –30, –50, and –70 kPa) using subsurface drip irrigation in 1997 and 1998. Onions were grown on 1.1-m beds with two double rows spaced 0.56 m apart and a drip tape buried 13 cm deep in the bed center. Soil water potential was maintained at the five levels by automated, high-frequency irrigations based on SWP measurements at 0.2-m depth. Onions were evaluated for yiel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
39
0
3

Year Published

2005
2005
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 74 publications
(46 citation statements)
references
References 5 publications
2
39
0
3
Order By: Relevance
“…During the 2 years precipitation amounts were different, with that in 2006 being nearer to normal. It was found that marketable production was increased under more frequent irrigation 13. However, Shock et al 13 conducted their work under normal growing conditions for the location.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…During the 2 years precipitation amounts were different, with that in 2006 being nearer to normal. It was found that marketable production was increased under more frequent irrigation 13. However, Shock et al 13 conducted their work under normal growing conditions for the location.…”
Section: Resultsmentioning
confidence: 99%
“…It was found that marketable production was increased under more frequent irrigation 13. However, Shock et al 13 conducted their work under normal growing conditions for the location. The relatively more normal, drier conditions in Oklahoma appeared to be more conducive to plant development and deposition of most nutrients in bulbs.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In this case, the curve number used was 82: Hydrologic soil group "C"; "Good" hydrologic condition; "Row crops"; and "Contoured labour" (land slope < 2%). The first K y stage of onion [K y (i)] is divided in two substages to differentiate between establishment [K y (i )] (where no high stress should by applied) and vegetative development [K y (i )] (where higher stress is allowed) (Shock et al, 2000;Bekele and Tilahun, 2007) (Fig. 3).…”
Section: Typical Meteorological Year Methodology For Forecasting Irrimentioning
confidence: 99%
“…The irrigation amounts in the area under no deficit conditions should be around 700 mm (López-Urrea et al, 2009a). Results of several deficit irrigation (DI) experiments (Shock et al, 2000;Martín de Santa Olalla et al, 2004;Kadayifci et al, 2005;Bekele and Tilahun, 2007) indicate that to obtain maximum yield it is necessary to avoid water deficit, especially during the bulb development, while during the vegetative and ripening periods the crop appears to be less sensitive to water deficit.…”
Section: Introductionmentioning
confidence: 99%